INTEGRATION OF ICT IN THE SOCIAL SCIENCE EDUCATION CASE IN SECONDARY SCHOOL IN MADAGASCAR AND ENVIRONMENTAL EDUCATION - IAVO, RAMANANARIVO; Wiyanarti, Erlina; Nana, Supriatna (Universitas Pendidikan Indonesia, 2021)
This article will attempt to identify teachers’ skills and competence in introducing new information and communication technologies (NICT) in schools in Madagascar. The development of information and communication technologies (ICT) has an important contribution to education especially in social education, especially in the learning process. Social studies as sciences related to the development of human life both in terms of social relations, culture, history, law, and its interaction with the natural environment are closely associated with the level of human civilization, including current technology. All aspects of human life are studied in the humanities. In this regard, we will address the 1) The use of the TICE product creates a positive reflex towards the environment, which would result in an enhancement of environmental education; 2) The use of ICT allows for more effective teaching through innovation in methods and the use of new teaching tools. All this should contribute to the mastery of active pedagogy. Therefore, to be able to clarify the learning material with the effects of research, so broad and constantly experiencing these developments, information and communication technologies (ICT) must for a purpose that thrives environmental education and seen as favorable in the learning of social science. Keywords: ICT, social studies, education